The use of artificial intelligence as a tool for efficiency and access to justice in a systematic literature review (Research, Society and Development, 2022)
In contemporary times, public organizations have directed their efforts toward replacing bureaucratic public administration with managerial public administration based on effective results. Within the scope of the Judiciary, this reality is linked to issues such as guaranteeing the fundamental rights of citizens, which, in order to be realized, require a change in attitude that ensures access to justice, embodied in an effective response from the Judiciary and within a perspective of reasonable duration of the process. In view of this, the discussions and the search for technological solutions to the inefficiency and slowness of proceedings, with the help of artificial intelligence tools, have been intensifying, nationally and internationally, since algorithms present good perspectives for the improvement of the jurisdictional provision and access to justice. The method used was a systematic review of quantitative and qualitative literature, conducted on the Web of Science, Scopus, and Theses and Dissertations Databases, using the last five years as a time frame. In the international research findings, possibilities were found such as intelligent readers, automated searches with e-discovery to access previous data, in addition to data mining and processes that can support the decision making of judges. In Brazil, it was found that there has been a significant evolution in the use of algorithms over the past five years, most of it supported by the system of judicial precedents and procedural screening. Finally, it is verified the importance of regulatory measures of ethical character, to be observed by artificial intelligence developers, in order to prevent unwanted reflexes.